Dialogisation of university education: experience of the Belarusian State University - Karol, Andrey D.; Morozova, Natalia I. (University Pedagogical Journal, 2021)
The article deals with the design and implementation of a heuristic-type education system based on a dialogue, focused not on transferring to the student the experience of humanity with subsequent assimilation and verification, but on the creation by each student of his own unique educational product. Such self-realisation of the student leads to the discovery of his own meanings, mission, the development of cognitive, creative, organisational and activity qualities of the individual. The student’s question acts as a methodological and methodological component of the goals, content, forms and methods of teaching, an assessment criterion. The article also reveals the experience of implementing the system of education of the dialogical type at the Belarusian State University. Particular emphasis is placed on improving the qualifications of teachers, based on their participation in organisational and activity seminars «Learning by discovery methodology: how to teach everyone differently, but the same way».
Keywords: creative education; key competencies; e-learning tools; educational process; heuristic learning; creative learning model; dialogue; creative learning system